Mojo Workin' : The Old African American Hoodoo System - Hazzard-Donald, Katrina, 1948- (Book collections on Project MUSE., 2013)
This book explores African Americans' experience and practice of the herbal, healing folk belief tradition known as Hoodoo. The author examines Hoodoo culture and history by tracing its emergence from African traditions to religious practices in the Americas. Working against conventional scholarship, the author argues that Hoodoo emerged first in three distinct regions she calls "regional Hoodoo clusters" and that after the turn of the nineteenth century, Hoodoo took on a national rather than regional profile. The spread came about through the mechanism of the "African Religion Complex," eight distinct cultural characteristics familiar to all the African ethnic groups in the United States. The first interdisciplinary examination to incorporate a full glossary of Hoodoo culture, this book lays out the movement of Hoodoo against a series of watershed changes in the American cultural landscape. The author examines Hoodoo material culture, particularly the "High John the Conquer" root, which practitioners employ for a variety of spiritual uses. She also examines other facets of Hoodoo, including rituals of divination such as the "walking boy" and the "Ring Shout," a sacred dance of Hoodoo tradition that bears its corollaries in the American Baptist churches. Throughout, the author distinguishes between "Old tradition Black Belt Hoodoo" and commercially marketed forms that have been controlled, modified, and often fabricated by outsiders; this study focuses on the hidden system operating almost exclusively among African Americans in the Black spiritual underground. -- Publisher's description.